Pengaruh Keterampilan Politik terhadap Kinerja Karyawan melalui Organizational Citizenship Behavior - GUNAEDI, NANANG; KISTYANTO, ANANG (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract Bak Jatim is a regional owned enterprise (BUMD) . This bank was estabilished on august 17,1961 in Surabaya, East Java. Several factors for improve employee performance can be through political skill and organizational citizenship behavior. This reserarch uses a quantitative approach. This research was conducted on 31 employees of Division human capital Bank Jatim central Surabaya. This research uses Partial Least Square (PLS) analysis. The purpose of this research is to test and analyze the role of organizational citizenship behavior as an intervening variable between political skill and employee performance. The result shows that political skill has no significant effect on employee performance. Political skill has a positive and significant effect on organizational citizenship behavior. Organizational Citizenship Behavior has positive and significant effect on Employee Performance. Organizational citizenship Behavior interferes with the influence between Poitical skill on employee performance. Keywords: political skill, organizational citizenship behavior, employee performance